Quality-monitoring program for bar-code-assisted medication administration. - Mims E; Tucker C; Carlson R; Schneider R; Bagby J (American Journal of Health-System Pharmacy, 2009)
PURPOSE: The implementation of a quality-monitoring program that identifies and corrects problems associated with using a bar-code-assisted medication administration (BCMA) system is described. SUMMARY: In November 2004, the Bar Code Resource Office assembled a work group to develop a quality program to improve machine-readable, bar-coded medications. The project scope involved the development of a pharmacy-based quality program for unit-dose packaging and bar-code labeling to improve the scanning success rate of bar-coded medications at the point-of-care. Data were collected from facility-based BCMA coordinators at each medical center regarding specific reasons for bedside scanning circumvention, as well as successful scan rates in the pharmacy and at the bedside. The pharmacy and bedside scanning data were aggregated and the baseline of successful scans was determined to be 95%. The reported reasons for scanning circumvention were grouped into six categories: bar-code labeling, missing doses, labels not scanning, error messages, mispackaged medications, and mislabeled medications. The work group developed strategies to mitigate problems in each of the areas. As a result of this effort, the Department of Veterans Affairs created a directive that outlined the best practices for unit-dose packaging and labeling, as well as requirements for ongoing data collection and reporting. CONCLUSION: A quality-monitoring program that identified and provided best-practice recommendations corrected problems associated with using a BCMA system and improved bar-code labeling processes.